Laminar Forced Convective Heat Transfer Studies in Circular and Non-circular Ducts with Polyacrylamide Additives in Water-based Al2O3 Nanofluid - Tiong, Angnes Ngieng Tze (Curtin University, 2017)
Nanofluid enhances heat transfer but with increased pressure drop. Therefore, this research aims to improve the thermal-hydraulic efficiency of Al2O3 nanofluid by adding polyacrylamide additives. Polyacrylamide additives help to further enhance the heat transfer of nanofluid, thus improving the efficiency in the non-circular ducts. The optimum concentration is found to be 50 ppm polyacrylamide in 4% nanofluid. Besides, Nusselt number and friction factor correlations are also proposed for this new hybrid fluid in pipe flow.